Reformulação do cálculo do nível de dano econômico de insetos-praga da cultura da soja - Martins, Fábio Lucas Izaguirre (2018)
This thesis is about the reformulation of the calculation of the economic injury level of the soybean culture insects-pests, it was indebted in three chapters that complement each other and the themes were dissented under different prisms and forms of approaches. Three forms of writing were used for the chapters, one review, another as a meta-analysis and the last as a case study. The first chapter is a historical chronology of the economic injury level study - EIL, introducing the authors who are the pillars of the study. It was discussed nomenclatures, concepts, mathematical formulas and based on the knowledge developed in the research, it was suggested a new mathematical model for EIL calculation. In the second article, changes were made in the EIL calculation formula, modifications in the formulation of control costs, changes in the model of the rate of loss of yield were also considered, the efficiency of the chemical control and resistance of the environment, and finally, the damage in kg / ha caused by a bed bug / m² / day was estimated. The results of the simulation behaviors led to the development of a vast EIL database. In the third article, an application was made for decision making in soybean pest management, which was named Pre-MIP. The structure of the algorithm and the way of implementation was made so that farmers and consultants interact with the software in the easiest way possible. The layout for farmers is simplified and the interface to be used by consultants is more focused on research in a more technological environment in order to obtain results of more specific behaviors. The three chapters are innovative in that the first deals with a historical chronology on the subject, something scarce in Brazil. The second contains a new approach to EIL modeling, and a detailed study has been conducted in the form of a meta-analysis with a number of well-established research on bedbug damage. Finally, in the third article, a decision-making application was developed that proved to be efficient and easy to use by farmers and consultants. All these results are important as a reflection on soybean pests and can still be applied to other pests and crops.